Vivência do climatério em um grupo de mulheres de uma unidade de saúde da família - Zanotelli, Silvana dos Santos (2010)
This study investigated the climaterium experience in a women group linked to a Family Health Strategy Unit in Brazil. The general objective was: Understanding how women linked to the Family Health Strategy Unit in a town of the South of Brazil experience climaterium. The approach used was based in a descriptive qualitative field study. The data were collected by means of semi-structured interview, between March and August 2009 and had the participation of 13 women aging from 45 to 60 years old, climacteric period, according to the Health World Organization. The thematic analysis suggested by Minayo was used for the data analysis, generating two categories: women s perception on climaterium; Perceptions on sexuality in climaterium; Perceptions of self-image in climaterium; Knowledge construction on climaterium; Religious support and climaterium; Health service and the woman in climaterium. The findings of this study allow asserting that, currently, women experience climaterium in many different ways, and that the period experience is shaped by biological, social and cultural characteristics. Therefore, it is necessary that multiple factors which permeate women s life can be observed when assistance is provided to them, that women can be serviced in group, thus this way, through knowledge socialization and together with the health team support they have the possibility of experiencing climaterium in a more natural and calmer manner. It is important to (re) think the care nursing practice, articulated with other health professionals, so that they can implement strategic measures of assistance to women in climaterium, meeting their needs and leading them to an active and healthy life, with well-being and quality in this period as well.